Amoxicillin and Favipiravir Bio-Degradation by Aspergillus Flavus Fungus - Rana Hadi Hameed Al-Shammari; Shaimaa Satae M. Ali; Ayad M.J. Al-Mamoori (مجلة بغداد للعلوم, 2024)
The aim of this study is to isolate and characterize Amoxicillin and Favipiravir biodegrading fungi as well as determine their characteristics and degradation pathways. The antibiotic-degrading fungus A. flavus was isolated from polluted wastewater samples using standard Potato Dextrose agar and Czapek–Dox medium. The biodegradation method was investigated in previous mediums with (Amoxicillin and Favipiravir), as the sole carbon sources. Main degradation intermediates were analyzed by high-performance liquid chromatography (HPLC) and used to deduce the antibiotic degradation pathway of strain A. flavus fungal hyphae by Scanning Electron Microscopy before and after 7 days of treatment to find out the accumulation of the antibiotic and morphological changes in fugal hyphae. Fungi can use antibiotics as their sole carbon source. Maximum biodegradation was observed at 91% at the lowest concentration of Amoxcillin. According to HPLC results, the A. flavus retention time of standard Amoxicillin was 8.12 minutes after biodegradation, when it broke down into other compounds with retention times of 3.75 minutes by 73.25%, 5.81 minutes by 16.44%, and 8.5 minutes by 8.59. According to standard Favipiravir retention time, it appeared in 3.97 minutes, but after treatment, two materials appeared in 2.20 minutes by area: 62.58% and in 6.16 minutes by area: 20.15%. Scan Electron microscopy images regarding treatment with Favipiravir by A. flavus showed an accumulation of particles on the fungal hyphae. This investigation gives insights into the improvement of bio-remediation methods to remove antibiotics from wastewater before they are discharged into rivers.